Development of high-performance cathodes for IT-SOFCs through beneficial interfacial reactions - Zhou, Y.; An, B.; Guo, Y.; Ran, R.; Shao, Zongping (Elsevier Inc., 2009)
We propose a new way to develop high-performance cathodes for IT-SOFCs by utilizing the interfacial reactions. SrCoOx was selected as the starting electrode material, which took a vacancy-ordered 2H BaNiO3-type structure and showed negligible ionic conductivity and low electrical conductivity. Phase reactions between SrCoOx and Sm0.2Ce0.8O1.9 happened at 900 °C or higher, resulting in the incorporation of Sm and Ce into its lattice structure. This promoted the phase transition to a cubic perovskite and led to substantial increase in the electrical conductivity and oxygen mobility of the electrode. By utilizing such phase reactions, the SrCoOx + Sm0.2Ce0.8O1.9 composite was developed into a high performance electrode with a low area specific resistance of 0.08 O cm-2 at 650 °C. An anode-supported cell with such electrode delivered a peak power density of 795 mW cm-2 at 600 °C. © 2009 Elsevier B.V. All rights reserved.